Terrestrial 10Be and electron spin resonance dating of fluvial terraces quantifies quaternary tectonic uplift gradients in the eastern Pyrenees. (1st August 2018) - Delmas, Magali; Calvet, Marc; Gunnell, Yanni; Voinchet, Pierre; Manel, Camille; Braucher, Régis; Tissoux, Hélène; Bahain, Jean-Jacques; Perrenoud, Christian; Saos, Thibaud; ,
Abstract: The 120 km -longTêt River flows out of the Pyrenees to the Mediterranean. By displaying a mappable sequence of Quaternary alluvial units between the Pleistocene frontal moraines of the high range and the offshore sedimentary depocentres, its 1400 km 2 watershed is well suited to quantifying gradients of topographic uplift. Five main generations of terrace treads had previously been inferred from constrasts in regolith weathering features, but here we present the first radiometric age constraints based on 15 ESR sediment burial ages covering the full sequence, and 3 vertical TCN age profiles restricted to three mid-sequence terraces. Analytically robust results were obtained for the oldest and uppermost terrace T5 (ESR age: 1099 ± 179 ka), for T3b (ESR age: 374 ± 47 ka, ∼MIS 10), and for T2 (ESR age: 174 ± 44 ka, ∼MIS 6). These results are consistent with the contrasts in weathering grade of the deposits. The TCN profiles only yielded minimum exposure ages but provided precise post-depositional denudation rates for the fluvial terrace treads. The land-to-sea geometry of the chronosequence also provided clues about valley incision rates in response to topographic uplift during the last ∼1 Ma. Based on a critical review of similar data obtained for other Mediterranean and Atlantic watersheds in the Pyrenees, the full regional correlation reveals that post-orogenic topographic uplift was substantial and relatively uniform throughout the entire mountain range. Patterns and magnitudes suggest a shared, probably subcrustal driving mechanism of Neogene and Quaternary mountain growth, with only subsidiary influence from isostasy, and climatic forcing. Highlights: The 120 km Têt River (Pyrenees) connects 2.8 km summits to the Mediterranean Sea. Radiometric ages were obtained for five alluvial terrace levels in the Têt watershed. The Pleistocene valley incision chronology documents climatic and tectonic controls. Similar fluvial sequences are reviewed, revised, and correlated across the entire Pyrenees. The magnitude of regional uplift since the early Pliocene has exceeded 700 m.